Karakteristik Kimia Dan Organoleptik Set Yogurt Dengan Penambahan Tepung Daun Kelor (Moringa Oleifera) - karamy, Aliefa bintan; quddus, Ati atul; tubagus, Robi (Jurnal Pangan dan Gizi, 2024)
Moringa leaf flour is rich in nutrients such as protein and calcium, which are beneficial for individuals with stunting and help enhance food product diversification. A study involving the addition of Moringa Oleifera leaf flour to yoghurt aims to assess its impact on chemical and organoleptic characteristics. The experiment utilized a Completely Randomized Design with three levels of Moringa leaf flour addition: 1% (P1), 2% (P2), and 3% (P3). The results indicate that the addition of Moringa leaf flour significantly affects ash content, lactic acid, protein, fat, and calcium levels in yoghurt. Furthermore, this addition also significantly influences taste but not aroma, texture, colour, or overall product perception